Automatic medication dispensing prototype - Martinez Baquero, Javier Eduardo; Jimenez Moreno, Robinson; Bejarano Restrepo, José Miguel (LACCEI, 2025)
This paper describes the design of an automatic pill dispenser, which is developed from a CAD model, which is then 3D printed. Subsequently, the device is assembled incorporating the necessary electronics for its operation, using an ESP32 microcontroller card. To facilitate the control of the dispenser, a mobile application is created using APP Designer, which allows to manage and activate the servomotors responsible for the dispensing of the tablets. The mobile application facilitates the user's interaction with the system, making it possible to program and control the dispensing of medication in a precise manner. In addition, the effectiveness of the module is validated when used through the mobile application, ensuring its correct functioning in the dispensing process. This design not only optimizes medication administration, but also incorporates safety measures to prevent accidents, especially in environments with children, providing additional control to prevent minors from having unauthorized access to medications. In this way, the system not only improves accuracy and efficiency in tablet dispensing, but also offers a level of protection, ensuring safe and proper use of the dispenser